(3OjhGf GHf HcJGTs - (3Ndjd Hf EHQGgje HcJGTs
(3ChdgG (B:s
(3CeG HYO(B: (3ajbhd GdYHO GdabjQ deG VGb Ydqj aj HdGOj GdeYGT dhjJ YfGf GdJhLg Edi HZOGO OGQ GdSdGe dcj CHdZ GdebUhO hGdoeQGO, hcKJ ajgG eOg eOjOg s
(3BNQgG (B:s
(3de fQ eKdg edjMG ceG de fdb eKd GdSYjO TgeG QVjG s
(3JTJed Ydi JSY hYTQjf bUjOI aj eOM hGdj HZOGO SYjO HGTGs
(3heQJHI Ydi MQha GdoeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B43 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdCOHs